2017
DOI: 10.21111/iej.v3i1.1383
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Strategi Penghimpunan Dana Zakat, Infak, dan Sedekah (Studi kasus di LAZ Ummat Sejahtera Ponorogo)

Abstract: One of the Zakat Institution in Ponorogo is LAZ Ummat Sejahtera Ponorogo, which has a muzakki 1.500 people in Ramadan, but except that month, it has 350-400 people of muzakki. The Aim of this research is to identify the preferences and factors influencing the Muslims of Ponorogo in paying Zakat infaq,shodaqoh and to identify the strategy of accumulating zakat infak shodaqoh at LAZ Ummat Sejahtera Ponorogo. The method that used in this research is mixed method or trianggulation method. Also Quantitative researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…In this topic, researchers generally discuss the factors that influence people in paying zakat from the perspective of accounting information. This topic has been researched by, Jayanto & Munawaroh (2019), Mukhibad, Fachrurozie, & Nurkhin (2019), Musqari & Huda (2018), Ghani et al, (2018), Sutomo, Najib, & Djohar (2017), Ahmad & Rusdianto, (2018), Djayusman et al, (2017), Ikhwandha & Hudayati, (2019), Mustafa et al, (2013), Mutmainah, (2015, Nasim & Syahri Romdhon, (2014), Komala, (2017, Restuningtyas et al, (2017). Accounting information research has not become the main focus of researchers, in which case the accounting information variable is only part of the variables studied.…”
Section: Accounting Information Of Zakat Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this topic, researchers generally discuss the factors that influence people in paying zakat from the perspective of accounting information. This topic has been researched by, Jayanto & Munawaroh (2019), Mukhibad, Fachrurozie, & Nurkhin (2019), Musqari & Huda (2018), Ghani et al, (2018), Sutomo, Najib, & Djohar (2017), Ahmad & Rusdianto, (2018), Djayusman et al, (2017), Ikhwandha & Hudayati, (2019), Mustafa et al, (2013), Mutmainah, (2015, Nasim & Syahri Romdhon, (2014), Komala, (2017, Restuningtyas et al, (2017). Accounting information research has not become the main focus of researchers, in which case the accounting information variable is only part of the variables studied.…”
Section: Accounting Information Of Zakat Institutionsmentioning
confidence: 99%
“…Some researchers reveal the management board aspect. Ghani et al (2018), and Nasim & Romdhon (2014) found that the management board affects the trust of muzaki, Djayusman et al (2017) found that services affect the intention to pay zakat, Widarwati et al (2017) found that CRM affects the performance of zakat fund collection. The board of capital, disclosure practice and governmental model were tested by Mustafa et al (2013).…”
Section: Accounting Information Of Zakat Institutionsmentioning
confidence: 99%
“…Penelitian kualitatif ini digunakan teknik pengumpulan data yang meliputi observasi, wawancara mendalam serta kajian literatur. 1 Penelitian ini menggunakan pendekatan normatif yang dilakukan dengan 1 Djayusman, R. R., Afif, M., Triyawan, A., & Abduh, F. (2017)…”
Section: Literature Reviewunclassified
“…Pembentukan unit pengelola zakat ini bisa saja diimplementasikan dalam pengelolaan zakat di Indonesia ketika pengurus yang ada di dalam unit pengelola zakat ini berjalan mandiri tanpa ada campur tangan dari pemerintah, dan bisa bersinergi dengan lembaga amil zakat yang ada. 18 Rencana Program, Kegiatan, dan Indikator Kerja BAZNAS Kabupaten Majalengka periode 2016-2021 berbasis 5 pilar, 19 Baznas Kabupaten Majalengka dalam pengelolaan zakatnya mengikuti sistem pengelolaan yang dilakukan oleh BAZNAS Pusat. Sehingga strategi pencapaian target pengumpulan dan pendistribusian zakat dan khususnya kerangka pengelolaannya mengikuti model-model nasional.…”
Section: A Manajemen Zakat DI Baznas Kabupaten Majalengka Pasca Undaunclassified